Repercussions in Spanish deontology in light of the rise of low cost dental clinics - de la Parte-Serna, Alejandro Carlos (Acta Bioethica, 2022)
The change in deontological health care model in Spain has led to the proliferation of huge dental franquises or low cost dental clinics. This type of settings generally engages customers by aggressive advertising campaigns, establishing financing with banks and reducing the agreed initial budget. In the last years, the Ethical and Deontological Commission of the Official College of Dentists and Stomatologists of Aragon has noticed a significant increase of claims by patients attending this type of clinics. One of the most striking cases has been the closing of iDental, which led thousands of patients without finishing dental treatment. This study pretends updating the deontological repercussions that these clinics have in the Autonomous Community of Aragon.